THE ROLE OF FINANCIAL LITERACY AND FINANCIAL INCLUSION ON STUDENTS ENTREPRENURIAL MOTIVATION - Islawati Islawati; Junaidi Junaidi; Rahmawati, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
The high unemployment rate and suboptimal levels of financial literacy and financial inclusion strongly correlate with the low number of entrepreneurs in Indonesia. Growing interest and motivation to become entrepreneurs among millennials and students is a challenge for both the government and universities. The sample consists of 310 participants who filled out the questionnaire. This study employed structural equation modelling (SEM) to scrutinize the research hypotheses. The results of this research confirm that financial inclusion and financial literacy have a significant and positive influence on entrepreneurial self-efficacy, which subsequently enhances students' entrepreneurial intentions. Furthermore, a positive and significant relationship exists between financial inclusion and financial literacy. Practical implications: This research can serve as a reference for government and university policy makers, particularly in their efforts to increase the number of entrepreneurs among students.